Catalisadores bimetálicos para reforma a seco de metano e anodos de células a combustível de óxido sólido - Souza, Glageane da Silva (2018)
In the search for renewable and environmentally friendly energy sources, hydrogen production and solid oxide fuel cell (SOFC) research have been prominent. Nickel and gadolinia doped ceria (Ce1-xGdxO2-? - CGO) based anodes have presented good electrochemical performance at intermediate temperatures (600-800 °C), allowing the direct oxidation of gases with hydrocarbons. Precursors of nickel, copper and cobalt bimetallic cermets (ceramic-metal composites) were obtained by the one-step synthesis method to evaluate their electrochemical performances as SOFCs anodes and to evaluate their catalytic behavior in dry methane reforming. NiO-Ce0.9Gd0.1O1.95 (NiO-CGO), NiCuO-CGO and NiCoO-CGO composite powders had their catalytic activities in reforming the methane, for hydrogen production, evaluated in the temperature range 400-800 ºC. These materials were also studied as solid oxide fuel cell anodes. Symmetrical anode/electrolyte/anode cells were prepared by screen-printing. The electrochemical activity was performed under typical anode operating conditions (reducing atmosphere in the temperature range between 650 and 750°C), using hydrogen and biogas as fuels. X-ray diffraction (XRD) analysis of powders calcined at 700 °C confirmed the attainment of NiO (NaCl-type), Co3O4 (spinel-type), CuO (tenoritetype) and Ce0.9Gd0.1O1.95 (fluorite-type). The crystallite size analysis indicated the obtaining of nanometric powders. The cobalt-based samples presented specific area values (evaluated by the BET method) higher than those of copper-based samples. Temperature programmed reduction (TPR) analysis indicated that the reducibility of the Ni-containing phase and its interaction with the CGO support are influenced by the presence and amount of cobalt and copper. The sample Ni0.2Co0.8O-CGO (NiCo0.8) showed high reduction capacity and strong metal/support interaction. The Rietveld refinement analysis for the reduced catalysts confirmed the presence of the Ni-Co alloy. These factors played a key role in enhancing catalytic activity and suppressing carbon deposition. The characterization of the catalysts after reaction by thermogravimetry and differential scanning calorimetry (TG-DSC) showed a better resistance to carbon deposition for NiCo catalysts. These catalysts showed higher conversions of CH4 and CO2 than NiCu and NiCGO catalysts. The NiCo0.8 catalyst showed a slightly higher CH4 conversion, better reaction selectivity between 600 and 750°C and better resistance to carbon deposition than Ni0.6Co0.4O-CGO (NiCo0.4). The methane reforming reaction with CO2 seems to be more favorable in the presence of the NiCo0.8 catalyst. The electrochemical characterization using impedance spectroscopy showed that the same electrode presents different electrochemical behaviors in hydrogen and biogas. In terms of overall behavior, NiCu0.8 is better than CuCGO in hydrogen. The inverse occurs in biogas, where the CuCGO anode performance is twice that of NiCu0.8. The calculation of the activation energies indicates that the complexity of the dry reforming of methane limits the electrochemical activity of the anodes in biogas.